A Case Report of Lhermitte-Duclos Disease in a 10-Month-Old Child Presenting with Hydrocephalus - Tamrakar, Abhishek; Gurung, Pritam; Acharya, Samir; Rajbhandhari, Pravesh; Pant, Basant (Nepal Journal of Neuroscience, 2019)
Lhermitte–Duclos Disease is a rare entity characterized by diffuse or focal enlargement of cerebellar folia. Clinical manifestations are usually related to a mass effect and secondary obstructive hydrocephalus. Increased intracranial pressure symptoms and cerebellar symptoms are the most frequent patient complaints. We present a 10-month-old male child with his mother who presented to the outpatient department with complaints of enlargement of size of head since the last one week. Magnetic Resonance Imaging scan revealed the features of Lhermitte–Duclos Disease involving the right cerebellar hemisphere with marked post contrast gyral enhancement. He underwent endoscopic third ventriculostomy. Lhermitte–Duclos Disease is very rare in early childhood and should be considered in the differential diagnosis of posterior fossa lesions.